Remarkable Changes of the Acidity of Bound Nitroxyl (HNO) in the [Ru(Me3[9]aneN3)(L2)(NO)]n+ Family (n = 1-3). Systematic Structural and Chemical Exploration and Bioinorganic Chemistry Implications - Levin Rojas, Natalia (2018)
This work demonstrates that the acidity of nitroxyl (HNO) coordinated to a metal core is significantly influenced by its coordination environment. The possibility that NO- complexes may be the predominant species in physiological environments has implications in bioinorganic chemistry and biochemistry. This (apparently simple) result pushed us to delve into the basic aspects of HNO coordination chemistry. A series of three closely related {RuNO}6,7 complexes have been prepared and structurally characterized, namely [Ru(Me3[9]aneN3)(L2)(NO)]3+/2+, with L2 = 2,2′-bipyridine, 4,4′-dimethoxy-2,2′-bipyridine, and 2,2′-bipyrimidine. These species have also been thoroughly studied in solution, allowing for a systematic exploration of their electrochemical properties in a wide pH range, thus granting access and characterization of the elusive {RuNO}8 systems. Modulation of the electronic density in the RuNO fragment introduced by changing the bidentate coligand L2 produced only subtle structural modifications but affected dramatically other properties, most noticeably the redox potentials of the {RuNO}6,7 couples and the acidity of bound HNO, which spans over a range of almost three pH units. Controlling the acidity of coordinated HNO by the rational design of coordination compounds is of fundamental relevancy in the field of inorganic chemistry and also fuels the growing interest of the community in understanding the role that different HNO-derived species can play in biological systems.